Development of an Aerobic Training Model for Volleyball Players Endurance at SMP Negeri 37 Tebo Regency in Extracurricular Activities - Dian Estu Prasetyo; Zuhar Ricky; Surya Nur Wahyu NIgsih (Program Studies of Physical Education, Faculty of Teacher Training and Education, Musamus University, 2023)
Objectives. This research was motivated by the lack of physical condition of volleyball players at SMPN 37, especially regarding physical endurance. This research aims to develop an endurance training model that will also increase the endurance of volleyball players at junior high school. This model was developed use the ADDIE model,analysis, planning, development, and implementation, which consists of 5 stages: analysis, planning, development, implementation, and evaluation. Materials and methods. These five stages are carried out through training program analysis, material analysis, and analysis of volleyball player characteristics. Then, the validation test was carried out by three validators, namely two expert team validators and one language validator. The practicality test was carried out by a volleyball coach and 12 volleyball players. After the model was categorized as valid and practical, an effectiveness test was carried out by carrying out a multistage fitness test (bleep test). Results. The results of research on the development of an aerobic training model for the endurance of volleyball players in the validity test obtained percentage data with an average of 86.19% categorized as very valid, practicality tests by volleyball coaches with a percentage of 90%, and players with a percentage of 83.88% categorized as very practical. In comparison, the effectiveness test was 83% in the very effective category. Conclusion. Based on the results obtained, the aerobic training model for endurance volleyball players is categorized as valid, practical, and effective, so it can be concluded that it can be applied to endurance volleyball players. This model is also an alternative form for trainers and teachers delivering material and exercises.